Freundlich isotherm equilibrium equastions in determining effectiveness a low cost absorbent to heavy metal removal in wastewater (Leachate) at Teluk Kitang landfill, Pengkalan Chepa, Kelantan, Malaysia - Ismail, Mohamad Ghazi; Chan, Ngai Weng; Abdul Rahman, Haliza; Zakaria, Nor Azazi (American Research Institute for Policy Development, 2013)
Problem Statement: Landfill site at Kg. Teluk Kitang were fully utilized in around 14 years ago. The method adopted was not fit a right landfills which do not have the bottom of the landfill liner. In the absence of this liner layer leachate seepage occurs causing so bad. The presence of leachate into the soil can interfere with clean groundwater can cause heavy metal content increased and could endanger the human health of a long period of time. Removal of heavy metals such as Iron (Fe2+), Copper (Cu2+) and Zinc (Zn2+) from leachate was studied using granular activated carbon, fly ash, limestone and granular activated carbon mixture.